Analytical Study of the Correlation between Consumer Price Index and Inflation in Malaysia - Mazlan, Nur Aziera Izzaty; Muhammad Basri, Cik Sri Mazzura (Enhanced Knowledge in Sciences and Technology, 2026)
The measurement of inflation is central to the study and the formulation of any economic policy, and the Consumer Price Index (CPI) has become the primary tool to measure the change in the price levels in Malaysia. This study analyzed the correlation between CPI and inflation in three economic periods such as before the COVID-19 pandemic, during the COVID-19 pandemic and after the COVID-19 pandemic. Time-series analysis is used to analyze monthly CPI and inflation data that are available at the Department of Statistics Malaysia (DOSM). The Augmented Dickey-Fuller (ADF) test is used to test stationarity, correlation and regressions analysis is carried out to determine the direction, strength and explanatory power of the CPI-inflation relationship. The findings indicate that there is a significant positive relationship between CPI and inflation during the COVID-19 pandemic and before the COVID-19 pandemic, but there is no significant linear relationship after the COVID-19 pandemic. These results imply that whilst CPI is useful in monitoring inflation in both stable and crisis times, it is not effective in monitoring inflation during periods of economic recovery, which suggests that CPI-based measure of inflation must be carefully interpreted.